Evolution and role of mergers in the BCG–cluster alignment. A view from cosmological hydrosimulations. Issue 2 (20th May 2020) - Ragone-Figueroa, C; Granato, G L; Borgani, S; De Propris, R; García Lambas, D; Murante, G; Rasia, E; West, M
ABSTRACT: Contradictory results have been reported on the time evolution of the alignment between clusters and their brightest cluster galaxy (BCG). We study this topic by analysing cosmological hydrosimulations of 24 massive clusters with $M_{200}|_{z=0} \gtrsim 10^{15}\, \rm {\, M_{\odot }}$, plus 5 less massive with $1 × 10^{14} \lesssim M_{200}|_{z=0} \lesssim 7 × 10^{14}\, \rm {\, M_{\odot }}$, which have already proven to produce realistic BCG masses. We compute the BCG alignment with both the distribution of cluster galaxies and the dark matter (DM) halo. At redshift z = 0, the major axes of the simulated BCGs and their host cluster galaxy distributions are aligned on average within 20°. The BCG alignment with the DM halo is even tighter. The alignment persists up to z ≲ 2 with no evident evolution. This result continues, although with a weaker signal, when considering the projected alignment. The cluster alignment with the surrounding distribution of matter (3 R 200 ) is already in place at z ∼ 4 with a typical angle of 35°, before the BCG–cluster alignment develops. The BCG turns out to be also aligned with the same matter distribution, albeit always to a lesser extent. These results taken together might imply that the BCG–cluster alignment occurs in an outside–in fashion. Depending on their frequency and geometry, mergers can promote, destroy or weaken the alignments. Clusters that do not experience recent major mergers are typically more relaxed and aligned with their BCG. In turn, accretions closer to the cluster elongation axis tend to improve the alignment as opposed to accretions closer to the cluster minor axis.